Carbohydrates in drug discovery: 1. Methods for solid phase glycoconjugate synthesis. 2. Synthesis and evaluation of carbohydrate toll-like-receptor agonist conjugates for S. pneumoniae vaccines. - Nguyen, Son. (2017)
Abstract: This dissertation describes two major studies directed toward: 1) Thiophilic promoters for the direct transfer of resin-bound oligosaccharides to complex acceptors in solid-phase organic synthesis, and 2) Studies toward development of well-defined carbohydrate antigen-based S. pneumoniae vaccines. Chapter 1 provides some background in glycoconjugate synthesis and glycorandomization. Chapter 2 explains development of a method for the direct transfer of resin-bound glycans to complex aglycones. This method has the potential to permit the rapid glycorandomization of natural products through parallel synthesis. Chapter 3 and 4 provide details on my synthetic works on a multi-investigator project focused on developing a new approach to non-proteinogenic oligosaccharide-based vaccines. In this approach, the antigen is directly attached to a small molecule toll-like receptor agonist. By eliminating the need for adjuvants, this approach is anticipated to greatly reduce unwanted inflammatory responses commonly associated with many types of vaccines. The synthesis of three generations of carbohydrate toll-like-receptor (TLR) 7 agonist conjugate vaccine candidates will be described.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Chemistry.; Advisor: Clay Bennett.; Committee: Krishna Kumar, Samuel Thomas, and Isaac Krauss.; Keyword: Organic chemistry.